Pendampingan Kegiatan Literasi al-Qur’an di Pondok Pesantren Jabal Rahmah Kabupaten Gorontalo - Fikriyansyah Mantau; Fatimah Djafar; Rakhmawati Rakhmawati (ARDHI : Jurnal Pengabdian Dalam Negri, 2023)
Every Muslim is required to be able to read, write, and memorize the Quran and understand its contents and apply it in everyday life. Teachers as people who are handed over the responsibility by parents in educating and guiding their children to the Qur'an are also required to be able to understand the character of students and the rules of learning Qur'an literacy and even be able to create a harmonious and humanist relationship in learning so that there is involvement of students in every learning activity so that creativity from fun and meaningful learning is realized. The purpose of this service carried out by the abdimas team is to provide assistance and training for the teaching team, namely two Islamic boarding school teachers about models, methods and media as well as the learning environment. This service method is Asset Based Community Development (ABCD), an asset-based method, strength and developing community potential. The results of continuous assistance are able to realize the ability of students to read, write and memorize the Qur'an well in accordance with the targets set and even practiced in everyday life through activities to create harmonious and humanist relationships as a basis for understandin